Pengukuran Efektivitas Mesin Multiline Menggunakan Metode Overall Equipment Effectiveness di PT. MNO - Digna Arkamaya Trixie Pradipta; Herwin Suprijono (Program Studi Teknik Industri Universitas Setia Budi, 2025)
The food and beverage industry in Indonesia, especially powdered beverages, continues to grow rapidly along with increasing consumer demand for practical products with long shelf life. PT. MNO, as one of the companies in this field, faces challenges in maintaining the efficiency and productivity of its production machines. This study aims to analyze the effectiveness of multiline packaging machines using the Overall Equipment Effectiveness (OEE) method to identify factors that affect machine performance and provide recommendations for improvement. OEE is measured based on three main factors, namely availability rate, performance rate, and quality rate. Observations were made for 17 days on machines 11 and 12 in multiline room 4, with three different operational shifts, namely morning, afternoon, and night shifts. The results showed that the average OEE value of machine 11 was 94% and machine 12 was 88.9%, which met the ideal OEE standard of >85%. However, the performance rate of machine 12 was still below the standard of 92.1%, mainly due to high downtime, such as machine setup and label changes. Analysis using a fishbone diagram identifies the causes of low machine performance from the aspects of humans, machines, methods, and raw materials. Some of the main factors that affect machine performance include unstable machine settings, inappropriate sealer temperatures, and less than optimal operator skills. Recommendations for improvement include increasing routine machine maintenance, operator training to improve skills in setting and troubleshooting, and setting the sealer temperature more appropriately according to the characteristics of the label.